Ответы и объяснения

2012-06-18T19:10:06+04:00

(3^0.5x+7 -9)(log(5+2*x)=0

Приравняем каждый множитель к 0:

3^(0.5x+7) -9=0

3^0.5x+7=9

3^0.5x+7=3^2

0.5x+7=2

0.5x=-5

x=-10

log(5+2x)=0

5+2x=1

2x=-4

x=-2

2012-06-19T00:57:13+04:00

(3^0.5x+7 -9)(log(5+2*x)=0

Каждый множитель=0:            

                                                                    log(5+2x)=0

3^(0.5x+7) -9=0                                              5+2x=1

3^0.5x+7=9                                                    2x=-4

3^0.5x+7=3^2                                                 x=-2

0.5x+7=2

0.5x=-5

x=-10